Quality control of front-end planning for electric power construction: a collaborative process-based approach using systems engineering - Nguyen, Frank Bao Thai, author; Grigg, Neil, advisor; Valdes-Vasquez, Rodolfo, advisor; Gallegos, Erika, committee member; Glick, Scott, committee member (Colorado State University. Libraries, 2024)
Controlling construction costs in the electric power industry will become more important as the nation responds to new energy demands due to the transition from gasoline to electric vehicles and to emerging trends such as artificial intelligence and use of cryptocurrency. However, managing electric utility construction project costs requires that the risk of field change orders (FCOs) during construction be controlled. In the electric power industry, utility companies face increasing risk from FCOs, due to conversion from overhead to underground systems required by security and climate change factors, and subgrade work is more challenging and less predictable than the more visible overhead work. Change orders cause cost overruns and schedule slippages and can occur for reasons such as changes in scope of work, unforeseen jobsite conditions, modifications of plans to meet existing field conditions, and correction of work required by field inspectors to meet safety standards. The best opportunity to control FCOs comes during front-end planning (FEP) when conditions leading to them can be identified and mitigated. This study utilized systems engineering methodologies to address risk of FCOs in three phases: (1) defining the root causes and identifying severities of FCOs, (2) evaluating stakeholder responsibilities to find and mitigate root causes of FCOs, and (3) developing a process to identify and find solutions for the risk of FCOs. The first phase involved using a descriptive statistical analysis of the project database of an electric utility company to identify and analyze the magnitude, frequency, and causes of FCOs in overhead and underground electrical construction. The results showed that FCOs with added scopes occurred more frequently in underground projects than in overhead projects. The analysis also indicated that most causes of FCOs could be managed during the FEP process, and it laid a foundation for the next phase, to promote collaboration among stakeholders to allocate responsibility to identify and mitigate risk of FCOs. In the second phase, the study used Analytical Hierarchy Process methodologies to distribute weights of stakeholder votes to create an integrated metric of front-end planning team confidence that a desired level of quality had been achieved. This study was significant in that it showed how effectiveness of collaborative working relationships across teams during front-end planning could be improved to create a quality control metric to capture risk of FCOs. In the third phase, the study used results from the first two phases and additional tools based on Swimlane diagrams and logical relationships between tasks and stakeholders to formulate a quality control roadmap model. This model is significant because it creates a roadmap to enhance the effectiveness of interdisciplinary teamwork through a critical path of the FEP process. The roadmap model shows a streamlined process for decision-making in each phase of front-end planning to minimize risk of FCOs through a logical path prior to final design. While there have been efforts to improve the design process, this study is the first one known to the researcher to address quality control of FEP using a roadmap process for quality control in electric power construction projects. The primary contribution is to enrich the body of knowledge about quality control of FEP by creating a roadmap model based on systems engineering and enhancing the effectiveness of collaborative working relationships in a logical process that captures risk of FCOs early in the FEP process. Besides the contribution of a method to reduce the risk of FCOs, the study points to another important concern to the construction industry about safety on the jobsite. The contractor normally requires a time extension to complete the work due to an FCO, but to reduce the impact to the project schedule, overtime is normally provided to the construction workers to perform the task. Additional research on this issue is required, but it is apparent that due to the fatigue of long working hours, this overtime may impact the task performance as well as the physical and psychological well-being of the construction workers, and they may lose safety awareness and have higher risk of accidents on the construction site. Thus, reducing the risk of FCOs will lead to less overtime and is an effective way for the construction project team to reduce the risk of construction accidents.